Dampak Perubahan Iklim Terhadap Pola Tanam Dan Produktivitas Pertanian - Nurbaya (CV. SINAR HOWUHOWU, 2025)
Climate change poses a major challenge to the agricultural sector, particularly affecting cropping patterns and crop productivity. This study aims to examine the impact of climate change on cropping patterns and agricultural productivity, as well as to identify adaptation strategies employed by farmers. The methods used include field surveys, statistical analysis, in-depth interviews, and climate-agronomy modeling using DSSAT. The results indicate a shift in cropping patterns due to uncertain rainy seasons and a decline in rice and maize productivity caused by rising temperatures and changes in rainfall. Adaptation strategies implemented include adjustments in planting schedules, use of climate-resilient crop varieties, and crop diversification, although limited by access to technology and resources. Modeling simulations highlight the need for effective adaptation interventions to prevent future yield declines. This study provides recommendations for policy and technological development to enhance agricultural resilience to climate change.